THE EFFECT OF POPULATION GROWTH AND GROSS REGIONAL DOMESTIC PRODUCT (GRDP) ON THE LEVEL OF UNEMPLOYMENT IN THE CITY OF MAKASSAR - Fadhila Ratu Pratiwi (Jurnal Economic Resource, 2020)
Economic growth is always a concern in many aspects of community life including issues related to unemployment and production. Therefore, this research aims to determine the impact of population growth and GRDP on the unemployment rate in Makassar City. The data analysis is used multiple linear regression. The result of this research indicate that population growth has an impact on the unemployment rate in Makassar City, because the growth that occurs is caused by the productive population in age levels in the job seeker group. The GRDP growth in Makassar City is followed by an unemployment rate even though the figure is small.